Measurement of the branching fraction ratio B(B+c → ψ(2S)π+)/B(B+c) → J/ψπ+) - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
Using pp collision data collected by LHCb at center-of-mass energies √s=7 TeV and 8 TeV, corresponding to an integrated luminosity of 3 fb−1, the ratio of the branching fraction of the B+c→ψ(2S)π+ decay relative to that of the B+c→J/ψπ+ decay is measured to be 0.268±0.032(stat)±0.007(syst)±0.006(BF). The first uncertainty is statistical, the second is systematic, and the third is due to the uncertainties on the branching fractions of the J/ψ→μ+μ− and ψ(2S)→μ+μ− decays. This measurement is consistent with the previous LHCb result, and the statistical uncertainty is halved.
Im Titel ist "+" hochgestellt, "c" ist tiefgestellt, wobei "c" unter "+" steht
Gesehen am 03.08.2021
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, S. Wandernoth, A. Zhelezov [und viele weitere]